Resolving the scale dependency in laboratory and field weathering rates - Banwart, S.; Zhang, C.; Evans, Katy (Taylor and Francis Group, 2004)
Results from tracer studies in hydraulically-unsaturated column reactors containing mine rockdemonstrate that significant mass of pore water is relatively immobile. This water mass is retained within stagnant zones that do not contribute to advective transport of solutes in reactor effluent. Solutes other than the inert tracer in the reactor effluent arise from chemical dissolution of minerals that compose the mine rock. Results demonstrate that the weathering rates of individual minerals can be quantified, if the effect of aqueous speciation, heterogeneous chemical equilibria and retention of solutes within stagnant zones are all considered. These results support the hypothesis that retention of solutes within stagnant zones at field sites contributes to the commonly observed discrepancy in weathering rates determined at laboratory and field scale.